Epigallocatechin-3-gallate inhibits the plasma membrane Ca2+-ATPase: effects on calcium homeostasis - Ontiveros, Mallku Qhapaj (2021)
Epigallocatechin-3-gallate (EGCG) and other catechins are the bioactive compoundspresent in green tea. These bioactives have been shown to be responsible to healthbenefits of green tea such as antiarthritic and anti-inflammatory effects as well as beinginvolved in the prevention of cardiovascular diseases and cancer, among others.Different studies have shown that EGCG is involved in intracellular calcium (Ca2+)homeostasis in excitable and in non-excitable cells. These findings hint at plasmamembrane Ca2+-ATPase (PMCA) involvement, as it transports Ca2+ actively to theextracellular medium coupled to ATP hydrolysis, maintaining the cellular homeostasis.The aim of this study was to investigate the catechins effect on the activity of isolatedPMCA and the mechanism through which EGCG inhibits PMCA activity in the isolatedprotein and in living cells.Results showed that (a) among catechins that inhibited PMCA activity, the most potentinhibitor was EGCG; (b) the measurement of partial reactions of phosphorylation of PMCAshowed EGCG produced an increase in EP levels by a decrease in the rate of EPbreakdown rather than an increase in the phosphorylation rate; (c) PMCAdephosphorylation was sensitive to ADP favoring the E1P intermediate; (d) dockingsimulations proposed that EGCG may bind to a site in the A domain; (e) EGCG inhibitedPMCA activity in human embryonic kidney cells (HEK293T) that transiently overexpresshPMCA4, suggesting that the effects observed on isolated PMCA occur in living cells.In conclusion, this study reveals the mechanism by which EGCG inhibits hPMCA4 isoformand shows that EGCG can inhibit PMCA activity in living cells. Therefore, the relevance ofour study lies in the fact that the EGCG effects on Ca2+ homeostasis may involve theinhibition of PMCA among other mechanisms.